A multidisciplinary consensus on dehydration: definitions, diagnostic methods and clinical implications. (19th May 2019) - Lacey, Jonathan; Corbett, Jo; Forni, Lui; Hooper, Lee; Hughes, Fintan; Minto, Gary; Moss, Charlotte; Price, Susanna; Whyte, Greg; Woodcock, Tom; Mythen, Michael; Montgomery, Hugh
Abstract: Background: Dehydration appears prevalent, costly and associated with adverse outcomes. We sought to generate consensus on such key issues and elucidate need for further scientific enquiry. Materials and methods: A modified Delphi process combined expert opinion and evidence appraisal. Twelve relevant experts addressed dehydration's definition, objective markers and impact on physiology and outcome. Results: Fifteen consensus statements and seven research recommendations were generated. Key findings, evidenced in detail, were that there is no universally accepted definition for dehydration; hydration assessment is complex and requires combining physiological and laboratory variables; "dehydration" and "hypovolaemia" are incorrectly used interchangeably; abnormal hydration status includes relative and/or absolute abnormalities in body water and serum/plasma osmolality (pOsm); raised pOsm usually indicates dehydration; direct measurement of pOsm is the gold standard for determining dehydration; pOsm >300 and ≤280 mOsm/kg classifies a person as hyper or hypo-osmolar; outside extremes, signs of adult dehydration are subtle and unreliable; dehydration is common in hospitals and care homes and associated with poorer outcomes. Discussion: Dehydration poses risk to public health. Dehydration is under-recognized and poorly managed in hospital and community-based care. Further research is required to improve assessment and management of dehydration and the authors have made recommendations to focus academic endeavours. Key messages: Dehydration assessment is a major clinical challenge due to a complex, varying pathophysiology, non-specific clinical presentations and the lack of international consensus on definition and diagnosis. Plasma osmolality represents a valuable, objective surrogate marker of hypertonic dehydration which is underutilized in clinical practice. Dehydration is prevalent within the healthcare setting and in the community, and appears associated with increased morbidity and mortality.